Kajian Aplikasi Brainly Berdasarkan Prinsip dan Paradigma Interaksi Manusia dan Komputer - Aulia, Laila; Prasetio, Prasetio (Jurnal Media Teknik Elektro dan Komputer, 2024)
The Brainly application has a user interface that is user friendly and easy for users to understand. The suitability of icons, colors, feature layouts, and instructions means that users do not need to use guidebooks or get confused looking for application instructions, users only need to imitate behavior according to the knowledge they understand. Based on the results of the study through several aspects, namely aspects of human, technology, usability, and ergonomics. This application is in great demand by users or users, especially students because this application makes it easy to learn in a fun and interesting way with presentations that are not only in the form of text but contain content in other forms such as videos, animations, and practice questions on each topic. Then at the end of the lesson a report on learning outcomes with interesting technology is presented where the user can find out the extent of his ability on each topic being worked on. Apart from that, there is no doubt about its functionality, because Brainly is an online learning platform that provides experienced private teachers who can be easily found through its learning services.